2016
DOI: 10.1007/s00261-016-0725-8
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation of liver tumors: degree of tissue contraction as compared to RF ablation

Abstract: MW ablation of hepatic tumors produced significantly more contraction of tumor and ablated hepatic tissue compared to RF ablation. Tissue contraction should be taken into account during pre-procedural planning and assessing treatment response by comparing pre- and post-ablation images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…Thus, we surmise that greater water vaporization during microwave ablation was primarily responsible for the strain differences observed in this study. Even though only one setting of RF ablation was performed in this study, the significant tissue contraction difference between RF and microwave ablation was commensurate with other studies that measured and compared RF and microwave contraction using different techniques . The present study, as well as the other previous studies, demonstrates that tissue contraction during microwave ablation may have a more critical influence on the treatment outcome compared to RF ablation.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, we surmise that greater water vaporization during microwave ablation was primarily responsible for the strain differences observed in this study. Even though only one setting of RF ablation was performed in this study, the significant tissue contraction difference between RF and microwave ablation was commensurate with other studies that measured and compared RF and microwave contraction using different techniques . The present study, as well as the other previous studies, demonstrates that tissue contraction during microwave ablation may have a more critical influence on the treatment outcome compared to RF ablation.…”
Section: Discussionsupporting
confidence: 86%
“…This will allow the model to obtain relationships between different ablation therapies and the degree of tissue contraction, thus providing useful information during intervention planning. It will be especially useful to investigate tissue expansion observed in post clinical intervention of tumour organs [15].…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies on renal tumours reported tissue diameter contractions of -10 to 50% [13,14]. MWA and RFA on liver tumours have also reported both tissue contraction and expansion, the latter being observed more frequently during RFA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of cirrhosis and tumour pseudocapsules, the surrounding fibrotic liver of HCC acts as an oven, creating higher temperatures and prolonged cytotoxic temperatures (204). MWA produces more tissue and tumour contraction compared with RFA, something that needs to be accounted for during pre-procedural planning and when assessing treatment response (205).…”
Section: Microwave Versus Radiofrequency Ablationmentioning
confidence: 99%